Contour bunding technology-evidence and experience in the semiarid region of southern Mali - Zemadim, Birhanu; Traoré, Kalifa B.; Sanogo, Karamoko; Tabo, Ramadjita; Fischer, Gundula; Whitbread, Anthony M. (Cambridge University Press, 2022)
Land and water management practices have been widely implemented in rural Mali since the1980s to improve agricultural productivity and erosion control. Under conditions of recurring droughts, these practices are expected to increase farmers’ ability to cope with shocks. One of the most common practices applied in the central and southern parts of Mali is contour bunding (CB). In this study the impact of the CB technology is evaluated with a focus on biophysical and socio-economic benefits. Data were collected in two agro-ecologies of southern Mali and were generated through field experimentation and household survey. Field experimentation involved implementation of contour lines with farm ridges, agronomic trails and runoff and erosion measurements. Agronomic data was collected on sorghum, maize, groundnut and millet for three consecutive years (2015 to 2017). Socio-economic data on the use of CB was obtained from individual farmer surveys. CB involves the layout of contour lines with land leveling devices to identify points of equal elevation and construction of contour lines with draught animals and human labor. The majority of the labor input to construct and maintain the CB comes from adult men who are head of the household (58%) and youth male (33%). Results indicate that with the application of CB yield of crops was higher with the highest increase in grain yield and biomass obtained for maize and millet (P < 0.01). CB application was useful in retaining soil water and reduced erosion rate. In treatment fields, 162mmof rainfall per year was saved as soil moisture and on average 13,090 kg per hectare of soil was lost from farm fields without CB, and CB implementation significantly reduced the soil loss by 163% (P < 0.01). The improvements in crops yield and biomass, and the retention of soil nutrients positively changed farm level productivity conditions. The majority of farmers (78%) perceived higher income from the sale of crops grown on CB plots. These results suggest the landscape wide application of CB.